2018
DOI: 10.1111/cch.12558
|View full text |Cite
|
Sign up to set email alerts
|

Does integrated academic and health education prevent substance use? Systematic review and meta‐analyses

Abstract: Background: Prevention of substance (alcohol, tobacco, illegal/legal drug) use in adolescents

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…From a preventive perspective, one can conclude from these results that school is a highly relevant setting and that social networks of parents and friends should be considered. Recent scientific reviews have shown that parent-based interventions seem to have an effect on adolescent alcohol use ( Bo, Hai, & Jaccard, 2018 ; Kuntsche & Kuntsche, 2016 ), and a systematic review of school-based health education showed a small but significant effect ( Melendez-Torres et al, 2018 ). Additionally, more general school environment interventions that aim to improve relationships between staff and students, classroom engagement and students’ involvement in decision-making seem to have a positive, or even more positive, effect on students’ health and health-related behaviours ( Bonell, Parry, et al, 2013 ; Bonell, Wells, et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…From a preventive perspective, one can conclude from these results that school is a highly relevant setting and that social networks of parents and friends should be considered. Recent scientific reviews have shown that parent-based interventions seem to have an effect on adolescent alcohol use ( Bo, Hai, & Jaccard, 2018 ; Kuntsche & Kuntsche, 2016 ), and a systematic review of school-based health education showed a small but significant effect ( Melendez-Torres et al, 2018 ). Additionally, more general school environment interventions that aim to improve relationships between staff and students, classroom engagement and students’ involvement in decision-making seem to have a positive, or even more positive, effect on students’ health and health-related behaviours ( Bonell, Parry, et al, 2013 ; Bonell, Wells, et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The overall confidence in the results of 56 out of 72 reviews was rated ‘critically low’, 3234,37,40–48,6173,7781,8391,9496,99101,103113 10 reviews were rated ‘low’, 60,7476,82,92,93,98,102 one was rated ‘moderate’, 39 while six reviews were rated ‘high’ 4,35,…”
Section: Resultsmentioning
confidence: 99%
“…Seventy two reviews were included. Of these 34 investigated interventions based in an educational setting (pre-school, school and higher education), 4,34,35,3941,44,46,48,6084 three in a family setting, 8587 three in a community setting, 37,88,89 one in a church 90 and 31 in multiple settings. 32,33,36,38,42,43,45,47,91…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other systematic reviews and meta-analyses have found similar results on school-based prevention programs. For example, the systematic review by Tremblay et al (2020) found that 70% of the programs demonstrated reductions in the use of substances, including both alcohol and drugs; and the systematic review and meta-analysis by Melendez-Torres et al (2018) concludes that this type of intervention was broadly effective for reducing specific alcohol and drug use. However, opposite results have also been found.…”
Section: Discussionmentioning
confidence: 99%